Polyanion solid electrolyte, preparation method thereof and solid-state battery

By introducing polyanionic clusters and heterovalent cation doping into the solid electrolyte, the problem of low ion conductivity of existing solid electrolytes is solved, and efficient ion transmission and battery performance improvement is achieved.

CN119560625AActive Publication Date: 2025-03-04SHENZHEN MSU-BIT UNIVERSITY

Patent Information

Application Number
CN202510112170.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-04
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The low ionic conductivity of existing solid electrolytes limits their application in high-performance battery systems.

Method used

The chemical formula of polyanionic solid electrolyte is AaM(3-a)/m(SO4)bE1-bGc. A variety of polyanionic raw materials are mixed evenly through wet high-energy ball milling, and a variety of polyanionic clusters and heterovalent cation doping are introduced to promote ion transport.

Benefits of technology

The room temperature ion conductivity of solid electrolyte is significantly improved, reaching more than 0.1 mS cm-1, reducing the activation energy, and improving the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560625A_ABST
    Figure CN119560625A_ABST
Patent Text Reader

Abstract

The invention relates to a polyanion solid electrolyte, a preparation method thereof and a solid-state battery, and belongs to the field of energy storage batteries. The polyanion solid electrolyte is AaM (3-a) / m (SO4) bE1-bGc; a is one of Li, Na and K; m is one or more of Li, Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La and Y; e is one or more of SO4 < 2->, CO3 < 2->, NO3 <->, NO2 <->, PO4 < 3->, PO4 < 3->, CrO4 < 2->, MnO4 < 2->, SiO4 < 4->, SiO3 < 2->, BO3 < 3-> and TeO4 < 2->; g is a halogen element; a is equal to 0-3, b is equal to 0-1, c is equal to 0-1, and m is the valence state of M cations. The ion transmission capability of the polyanion solid electrolyte is enhanced, and the ionic conductivity is improved, so that the performance of a solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage batteries, and in particular to a polyanion solid electrolyte and a preparation method thereof and a solid-state battery. Background Art

[0002] In recent years, lithium-ion batteries have played an increasingly important role in the development of portable consumer electronics and new energy vehicles. However, the current commercial lithium-ion batteries are based on organic electrolyte systems, which are prone to leakage, combustion or even explosion accidents when hit or punctured, and there are major safety hazards, threatening people's property and personal safety, which limits the further development of new energy vehicles and other industries. In contrast, all-solid-state batteries use solid electrolytes (SSE), which have the advantages of high energy density and high safety. They have attracted widespread attention from all walks of life and are expected to become a new generation of energy storage batteries.

[0003] Solid electrolytes are generally divided into three categories: inorganic solid electrolytes (ISE), polymer solid electrolytes (SPE) and composite solid electrolytes (CPE). No matter which type of SSE, it has significant advantages and disadvantages. Although SPE has good flexibility and processability, its ionic conductivity is relatively low. Although CPE also has good flexibility and processability, and its ionic conductivity is better than SPE, its preparation process is complicated and performance optimization is difficult. ISE has high thermal stability, high mechanical strength and a wide operating temperature. At present, common types of SSE include halide SSE, sulfide SSE and oxide SSE. However, the above-mentioned types of ISE also have many disadvantages, such as large interface impedance and low ionic conductivity of oxide SSE, poor interface compatibility of halide SSE, poor air stability of sulfide SSE and reaction with electrode materials, which seriously limits their wide application in high-performance battery systems.

[0004] Therefore, the existing technology still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a polyanion solid electrolyte and a preparation method thereof and a solid-state battery, aiming to solve the problem of low ion conductivity of existing solid electrolytes.

[0006] The technical solution of the present invention is as follows: In a first aspect of the present invention, there is provided a polyanion solid electrolyte, wherein the chemical formula of the polyanion solid electrolyte is A a M (3-a) / m (SO4) b E 1-b G c ; Wherein, A is one of Li, Na, and K; M is one or more of Li, Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La, and Y, and M and A are different elements; E is SO4 2- ,CO3 2- , NO3 - , NO2 - , PO3 3- ,PO4 3- , CrO4 2- , MnO4 2- , SiO4 4- , SiO3 2- , BO3 3- ,TeO4 2- One or more of; G is one or more of F, Cl, Br, and I; a=0~3, b=0~1, c=0~1, and a, b and c are not 0, and m is the valence state of the M cation.

[0007] The second aspect of the present invention provides a method for preparing the polyanion solid electrolyte of the present invention, wherein when A is Li, the chemical formula of the polyanion solid electrolyte is Li a M (3-a) / m (SO4) b E 1-b G c , the Li a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: LiG, ME and Li2SO4 or LiE, MG and MSO4 are used as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the Li a M (3-a) / m (SO4) b E 1-b G c .

[0008] The third aspect of the present invention provides a method for preparing the polyanion solid electrolyte of the present invention, wherein when A is Na, the chemical formula of the polyanion solid electrolyte is Na a M (3-a) / m (SO4) b E1-b G c , the Na a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: NaG, ME and Na2SO4 or NaE, MG and MSO4 are used as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the Na a M (3-a) / m (SO4) b E 1-b G c .

[0009] In a fourth aspect of the present invention, a method for preparing the polyanion solid electrolyte of the present invention is provided, wherein when A is K, the chemical formula of the polyanion solid electrolyte is K a M (3-a) / m (SO4) b E 1-b G c , the K a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: Using KG, ME and K2SO4 or KE, MG and MSO4 as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball-milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the K a M (3-a) / m (SO4) b E 1-b G c .

[0010] A fifth aspect of the present invention provides a solid-state battery, which includes the polyanion solid electrolyte described in the present invention.

[0011] Beneficial effect: The present invention provides a polyanion solid electrolyte A a M (3-a) / m (SO4) b E 1-b G c , and its room temperature ionic conductivity can reach 0.1 mS cm -1Above. The wet high-energy ball milling used in the present invention can effectively mix a variety of polyanion raw materials evenly, which is conducive to high-temperature sintering reaction to obtain the final product. The polyanion clusters of various sizes in the lattice can bring about the distortion of the lattice, which is conducive to bringing more ion transmission channels. At the same time, the various rotational couplings between the polyanion clusters can effectively promote the transmission of ions in the solid electrolyte, which is conducive to improving ionic conductivity and reducing activation energy. In addition, the doping of high-valent cations can not only introduce cation vacancies, provide more jumping sites for ion migration, but also effectively weaken the Coulomb attraction of lithium, sodium, and potassium ions by anions, thereby improving the migration ability of lithium, sodium, and potassium ions in the lattice. The present invention adopts a variety of strategies to synergistically enhance the ion transmission capacity of the polyanion solid electrolyte, improve ionic conductivity, and reduce activation energy, so that it can be ultimately applied to the preparation of secondary batteries with high safety and high specific energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 XRD patterns of lithium-based monoanion SSE and lithium-based trimerion SSE.

[0013] Figure 2 These are the AC impedance spectra of lithium-based monoanion SSE and lithium-based trianion SSE.

[0014] Figure 3 This is a graph showing the limiting current density test results of lithium-based mono-anion SSE and lithium-based tri-anion SSE.

[0015] Figure 4 This is a graph showing the cycling test results of lithium metal symmetric batteries of lithium-based single polyanion SSE and lithium-based tripolyanion SSE.

[0016] Figure 5 This is a graph showing the cycling test results of lithium metal full batteries of lithium-based monopolyanion SSE and lithium-based tripolyanion SSE.

[0017] Figure 6 These are the electrochemical impedance spectroscopy (EIS) spectra of sodium-based double polyanion SSE and cation-doped sodium-based double polyanion SSE. DETAILED DESCRIPTION

[0018] The present invention provides a polyanion solid electrolyte and a preparation method thereof and a solid-state battery. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0019] The embodiment of the present invention provides a polyanion solid electrolyte, wherein the chemical formula of the polyanion solid electrolyte is A a M (3-a) / m(SO4) b E 1-b G c ; Wherein, A is one of Li, Na, and K; M is one or more of Li, Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La, and Y, and M and A are different elements; E is SO4 2- ,CO3 2- , NO3 - , NO2 - , PO3 3- ,PO4 3- , CrO4 2- , MnO4 2- , SiO4 4- , SiO3 2- , BO3 3- ,TeO4 2- One or more of; G is one or more of F, Cl, Br, and I; a=0~3, b=0~1, c=0~1, and a, b and c are not 0, and m is the valence state of the M cation.

[0020] The embodiments of the present invention can be applied to lithium-based, sodium-based and potassium-based polyanion solid electrolytes. The transport of lithium, sodium and potassium ions in SSE is affected by multiple factors such as ionic Coulomb effect, electronic Coulomb effect, defects, lattice space size, etc. The rotational coupling mechanism of polyanion clusters in SSE materials can effectively promote the transport of ions. By introducing a variety of polyanion clusters into the lattice of SSE materials, the transport of ions in SSE can be effectively regulated, thereby improving the ionic conductivity of SSE and reducing the activation energy.

[0021] The polyanion solid electrolyte A provided in the embodiment of the present invention a M (3-a) / m (SO4) b E 1-b G c, A is any one of Li, Na, and K elements, and M is one or more of Li, Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La, and Y elements. Doping with heterovalent ions or ions of different sizes will introduce structural disorder (or high entropy effect). After such cations M are doped into the lattice, they occupy the same lattice site with the carrier ions A. Doping with heterovalent ions will introduce additional charge compensation mechanisms. For example, when doping with Mg ions, since the valence state of Mg ions is +2 and the valence state of A ions is +1, the introduction of Mg ions will bring about an A ion vacancy (the principle of valence balance). The formation of such vacancy defects will enhance the flexibility of the lattice, increase the jumping sites of A ions, and make the diffusion path of A ions easier to open. In addition, the different sizes of doped ions will cause local lattice distortion, which can destroy the periodic static potential field, thereby reducing the energy barrier encountered by A ions during the diffusion process. In addition, by adjusting the doping ratio of M ions, the concentration of carrier A ions can be effectively adjusted, and the ionic conductivity can be further regulated. E is SO4 2- ,CO3 2- , NO3 - , NO2 - , PO3 3- ,PO4 3- , CrO4 2- , MnO4 2- , SiO4 4- , SiO3 2- , BO3 3- ,TeO4 2- One or more of them. Polyanion clusters are the structural framework of this type of solid electrolyte. By constructing a single or multiple polyanion structural framework, the lattice environment and ion diffusion kinetics of this type of solid electrolyte can be optimized. The introduction of multiple polyanions can change the size characteristics of the crystal structure. For example, the larger polyanion CrO4 2- and SO4 2- (2.4~2.6 Å) provides a high-strength local framework to ensure structural stability; while the small polyanion CO3 2-(1.8~2.0 Å) introduces a certain flexibility and lattice distortion. This balance helps to form channels in the lattice that are more suitable for the migration of A ions and reduce the energy barrier of the migration path. The chemical properties of different polyanions (such as electronegativity, bond length) will introduce different local potential environments. This diversity helps to form more migration paths for A ions, allowing A ions to choose the optimal path to diffuse. In addition, the rotational coupling mechanism between different types of polyanions will also promote the transport of carrier ions A. G is one or more of F, Cl, Br, and I. The high electronegativity of halogen elements will bring about a polarization effect in the local lattice, which can weaken the electrostatic interaction between A ions and the surrounding environment, making it easier for them to leave their original position and migrate.

[0022] Among them, for Li-based SSE, its chemical composition is Li a M (3-a) / m (SO4) b E 1-b G c ; Among them, a=0~3; b=0~1; c=0~1; M=Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La, Y; E= SO4 2- ,CO3 2- , NO3 - , NO2 - , PO3 3- ,PO4 3- , CrO4 2- , MnO4 2- , SiO4 4- , SiO3 2- , BO3 3- ,TeO4 2- ; G=F, Cl, Br, I.

[0023] For Na-based SSE, its chemical composition is Na a M (3-a) / m (SO4) b E 1-b G c ; Among them, a=0~3; b=0~1; c=0~1; M=Li, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La, Y; E= SO4 2- ,CO3 2- , NO3 - , NO2 - , PO3 3- ,PO4 3- , CrO4 2- , MnO4 2- , SiO4 4- , SiO32- , BO3 3- ,TeO4 2- ; G=F, Cl, Br, I.

[0024] For K-based SSE, its chemical composition is K a M (3-a) / m (SO4) b E 1-b G c ; Among them, a=0~3; b=0~1; c=0~1; M=Li, Na, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La, Y; E= SO4 2- ,CO3 2- , NO3 - , NO2 - , PO3 3- ,PO4 3- , CrO4 2- , MnO4 2- , SiO4 4- , SiO3 2- , BO3 3- ,TeO4 2- ; G=F, Cl, Br, I.

[0025] In one embodiment, the polyanion solid electrolyte is in the form of irregular particles, and the particle size distribution is below 10 μm.

[0026] The embodiment of the present invention provides a method for preparing the above-mentioned polyanion solid electrolyte, wherein when A is Li, the chemical formula of the polyanion solid electrolyte is Li a M (3-a) / m (SO4) b E 1-b G c , the Li a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: LiG, ME and Li2SO4 or LiE, MG and MSO4 are used as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the Li a M (3-a) / m (SO4) b E 1-b G c .

[0027] In one embodiment, the step of placing the evenly ground raw material into a ball mill for ball milling specifically includes: placing the evenly ground raw material into a ball mill, adding ball milling beads ten times the mass of the raw material, adding a wet milling solvent, the solvent is one of ethanol, isopropanol, n-hexane, acetone, methanol, ethylene glycol, cyclohexane, dichloromethane, and n-heptane, and the ball milling parameters are set to a rotation speed of 200-600 rpm and a time of 12-24 hours.

[0028] In one embodiment, the ball-milled material is placed in a vacuum environment at 50-120°C for heating and drying, and finally the dried material is placed in a container, transferred to a high-temperature furnace, and heated to a certain temperature (preferably 500-600°C) at a certain heating rate (preferably a heating rate of 5-10°C / min), and kept warm for 12-18 hours, and then cooled naturally or rapidly cooled to room temperature, and then the prepared solid is crushed and ground to obtain powdered Li a M (3-a) / m (SO4) b E 1-b G c .

[0029] In one embodiment, the LiG includes one or more of LiF, LiCl, LiBr, LiI; The ME includes Na2SO4, Na2CO3, NaNO3, NaNO2, Na3PO3, Na3PO4, Na2CrO4, Na2MnO4, Na4SiO4, Na2SiO3, Na3BO3, Na2TeO4, K2SO4, K2CO3, KNO3, KNO2, K3PO3, K3PO4, K2CrO4, K2MnO4, K4SiO4, K2SiO3, K3BO3, K2TeO4, Rb2SO4, Rb2CO3, RbNO3, RbNO2, Rb3PO3, Rb3PO4, Rb2CrO4, Rb2MnO4, Rb4SiO4, Rb2SiO3, Rb3BO3, Rb2TeO4, Cs2SO4, Rb2CO3, CsNO3, CsNO2, Cs3PO3, Cs3PO4, Cs2CrO4, Cs2MnO4, Cs4SiO4, Cs2SiO3, Cs3BO3, Cs2TeO4, BeSO4, BeCO3, Be(NO3)2, Be(NO2)2, Be3(PO3)2, Be3(PO4)2, BeCrO4, BeMnO4, Be2SiO4, BeSiO3, Be3(BO3)2, MgSO4, MgCO3, Mg(NO3)2, Mg(NO2)2, Mg3(PO3)2, Mg3(PO4)2, MgCrO4, MgMnO4, Mg2SiO4, MgSiO3, Mg3(BO3)2, CaSO4, CaCO3, Ca(NO3)2, Ca(NO2)2, Ca3(PO3)2, Ca3(PO4)2, CaCrO4, CaMnO4, Ca2SiO4, CaSiO3, Ca3(BO3)2, SrSO4, SrCO3, Sr(NO3)2, Sr(NO2)2, Sr3(PO3)2, Sr3(PO4)2, SrCrO4, SrMnO4, Sr2SiO4, SrSiO3, Sr3(BO3)2, BaSO4, BaCO3, Ba(NO3)2, Ba(NO2)2, Ba3(PO3)2, Ba3(PO4)2, BaCrO4, BaMnO4, Ba2SiO4, BaSiO3, Ba3(BO3)2, Al2(SO4)3, Al2(CO3)3, Al(NO3)3, Al(NO2)3, AlPO3, AlPO4, Al2(CrO4)3, Al2(MnO4)3, Al4(SiO4)3, Al2(SiO3)3, AlBO3, Al2(TeO4)3, Ga2(SO4)3, Ga2(CO3)3, Ga(NO3)3, Ga(NO2)3, GaPO3, GaPO4, Ga2(CrO4)3, Ga2(MnO4)3, Ga4(SiO4)3, Ga2(SiO3)3, GaBO3,Ga2(TeO4)3, In2(SO4)3, In2(CO3)3, In(NO3)3, In(NO2)3, InPO3, InPO4, In2(CrO4)3, In2(MnO4)3, I n4(SiO4)3, In2(SiO3)3, InBO3, In2(TeO4)3, La2(SO4)3, La2(CO3)3, La(NO3)3, La(NO2)3, LaPO3, LaP O4, La2(CrO4)3, La2(MnO4)3, La4(SiO4)3, La2(SiO3)3, LaBO3, La2(TeO4)3, Y2(SO4)3, Y2(CO3)3, Y(NO3)3, Y(NO2)3, YPO3, YPO4, Y2(CrO4)3, Y2(MnO4)3, Y4(SiO4)3, Y2(SiO3)3, YBO3, Y2(TeO4)3. ,

[0030] In one embodiment, the LiE includes one or more of Li2SO4, Li2CO3, LiNO3, LiNO2, Li3PO3, Li3PO4, Li2CrO4, Li2MnO4, Li4SiO4, Li2SiO3, Li3BO3, and Li2TeO4; The MG includes one or more of NaF, NaCl, NaBr, NaI, KF, KCl, KBr, RbF, RbCl, RbBr, RbI, CsF, CsCl, CsBr, CsI, BeF2, BeCl2, BeBr2, BeI2, MgF2, MgCl2, MgBr2, MgI2, CaF2, CaCl2, CaBr2, CaI2, SrF2, SrCl2, SrBr2, SrI2, BaF2, BaCl2, BaBr2, BaI2, AlF3, AlCl3, AlBr3, AlI3, GaF3, GaCl3, GaBr3, GaI3, InF3, InCl3, InBr3, InI3, LaF3, LaCl3, LaBr3, LaI3, YF3, YCl3, YBr3, and YI3; The MSO4 includes one or more of Na2SO4, K2SO4, Rb2SO4, Cs2SO4, BeSO4, MgSO4, CaSO4, SrSO4, BaSO4, Al2(SO4)3, Ga2(SO4)3, In2(SO4)3, La2(SO4)3, and Y2(SO4)3.

[0031] The embodiment of the present invention provides a method for preparing the above-mentioned polyanion solid electrolyte, wherein when A is Na, the chemical formula of the polyanion solid electrolyte is Na a M (3-a) / m (SO4) b E 1-b G c , the Na a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: NaG, ME and Na2SO4 or NaE, MG and MSO4 are used as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the Na a M (3-a) / m (SO4) b E 1-b G c .

[0032] In one embodiment, the step of placing the evenly ground raw material into a ball mill for ball milling specifically includes: placing the evenly ground raw material into a ball mill, adding ball milling beads ten times the mass of the raw material, adding a wet milling solvent, the solvent is one of ethanol, isopropanol, n-hexane, acetone, methanol, ethylene glycol, cyclohexane, dichloromethane, and n-heptane, and the ball milling parameters are set to a rotation speed of 200-600 rpm and a time of 12-24 hours.

[0033] In one embodiment, the ball-milled material is placed in a vacuum environment at 50-120°C for heating and drying, and finally the dried material is placed in a container, transferred to a high-temperature furnace, and heated to a certain temperature (preferably 500-600°C) at a certain heating rate (preferably a heating rate of 5-10°C / min), and kept warm for 12-18 hours, and then cooled naturally or rapidly cooled to room temperature, and then the prepared solid is crushed and ground to obtain powdered Na a M (3-a) / m (SO4) b E 1-b G c .

[0034] In one embodiment, the NaG comprises one or more of NaF, NaCl, NaBr, and NaI; The ME includes Li2SO4, Li2CO3, LiNO3, LiNO2, Li3PO3, Li3PO4, Li2CrO4, Li2MnO4, Li4SiO4, Li2SiO3, Li3BO3, Li2TeO4, K2SO4, K2CO3, KNO3, KNO2, K3PO3, K3PO4, K2CrO4, K2MnO4, K4SiO4, K2SiO3, K3BO3, K2TeO4, Rb2SO4, Rb2CO3, RbNO3, RbNO2, Rb3PO3, Rb3PO4, Rb2CrO4, Rb2MnO4, Rb4SiO4, Rb2SiO3, Rb3BO3, Rb2TeO4, Cs2SO4, Rb2CO3, CsNO3, CsNO2, Cs3PO3, Cs3PO4, Cs2CrO4, Cs2MnO4, Cs4SiO4, Cs2SiO3, Cs3BO3, Cs2TeO4, BeSO4, BeCO3, Be(NO3)2, Be(NO2)2, Be3(PO3)2, Be3(PO4)2, BeCrO4, BeMnO4, Be2SiO4, BeSiO3, Be3(BO3)2, MgSO4, MgCO3, Mg(NO3)2, Mg(NO2)2, Mg3(PO3)2, Mg3(PO4)2, MgCrO4, MgMnO4, Mg2SiO4, MgSiO3, Mg3(BO3)2, CaSO4, CaCO3, Ca(NO3)2, Ca(NO2)2, Ca3(PO3)2, Ca3(PO4)2, CaCrO4, CaMnO4, Ca2SiO4, CaSiO3, Ca3(BO3)2, SrSO4, SrCO3, Sr(NO3)2, Sr(NO2)2, Sr3(PO3)2, Sr3(PO4)2, SrCrO4, SrMnO4, Sr2SiO4, SrSiO3, Sr3(BO3)2, BaSO4, BaCO3, Ba(NO3)2, Ba(NO2)2, Ba3(PO3)2, Ba3(PO4)2, BaCrO4, BaMnO4, Ba2SiO4, BaSiO3, Ba3(BO3)2, Al2(SO4)3, Al2(CO3)3, Al(NO3)3, Al(NO2)3, AlPO3, AlPO4, Al2(CrO4)3, Al2(MnO4)3, Al4(SiO4)3, Al2(SiO3)3, AlBO3, Al2(TeO4)3, Ga2(SO4)3, Ga2(CO3)3, Ga(NO3)3, Ga(NO2)3, GaPO3, GaPO4, Ga2(CrO4)3, Ga2(MnO4)3, Ga4(SiO4)3, Ga2(SiO3)3, GaBO3,Ga2(TeO4)3, In2(SO4)3, In2(CO3)3, In(NO3)3, In(NO2)3, InPO3, InPO4, In2(CrO4)3, In2(MnO4)3, I n4(SiO4)3, In2(SiO3)3, InBO3, In2(TeO4)3, La2(SO4)3, La2(CO3)3, La(NO3)3, La(NO2)3, LaPO3, LaP O4, La2(CrO4)3, La2(MnO4)3, La4(SiO4)3, La2(SiO3)3, LaBO3, La2(TeO4)3, Y2(SO4)3, Y2(CO3)3, Y(NO3)3, Y(NO2)3, YPO3, YPO4, Y2(CrO4)3, Y2(MnO4)3, Y4(SiO4)3, Y2(SiO3)3, YBO3, Y2(TeO4)3. ,

[0035] In one embodiment, the NaE includes one or more of Na2SO4, Na2CO3, NaNO3, NaNO2, Na3PO3, Na3PO4, Na2CrO4, Na2MnO4, Na4SiO4, Na2SiO3, Na3BO3, and Na2TeO4; The MG includes one or more of LiF, LiCl, LiBr, LiI, KF, KCl, KBr, KI, RbF, RbCl, RbBr, RbI, CsF, CsCl, CsBr, CsI, BeF2, BeCl2, BeBr2, BeI2, MgF2, MgCl2, MgBr2, MgI2, CaF2, CaCl2, CaBr2, CaI2, SrF2, SrCl2, SrBr2, SrI2, BaF2, BaCl2, BaBr2, BaI2, AlF3, AlCl3, AlBr3, AlI3, GaF3, GaCl3, GaBr3, GaI3, InF3, InCl3, InBr3, InI3, LaF3, LaCl3, LaBr3, LaI3, YF3, YCl3, YBr3, and YI3; The MSO4 includes one or more of Li2SO4, K2SO4, Rb2SO4, Cs2SO4, BeSO4, MgSO4, CaSO4, SrSO4, BaSO4, Al2(SO4)3, Ga2(SO4)3, In2(SO4)3, La2(SO4)3, and Y2(SO4)3.

[0036] The embodiment of the present invention provides a method for preparing the above-mentioned polyanion solid electrolyte, wherein when A is K, the chemical formula of the polyanion solid electrolyte is K a M (3-a) / m (SO4) b E 1-b G c , the K a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: Using KG, ME and K2SO4 or KE, MG and MSO4 as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball-milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the K a M (3-a) / m (SO4) b E 1-b G c .

[0037] In one embodiment, the step of placing the evenly ground raw material into a ball mill for ball milling specifically includes: placing the evenly ground raw material into a ball mill, adding ball milling beads ten times the mass of the raw material, adding a wet milling solvent, the solvent is one of ethanol, isopropanol, n-hexane, acetone, methanol, ethylene glycol, cyclohexane, dichloromethane, and n-heptane, and the ball milling parameters are set to a rotation speed of 200-600 rpm and a time of 12-24 hours.

[0038] In one embodiment, the ball-milled material is placed in a vacuum environment at 50-120°C for heating and drying, and finally the dried material is placed in a container, transferred to a high-temperature furnace, and heated to a certain temperature (preferably 500-600°C) at a certain heating rate (preferably a heating rate of 5-10°C / min), and kept warm for 12-18 hours, and then cooled naturally or rapidly cooled to room temperature, and then the prepared solid is crushed and ground to obtain a powdered K a M (3-a) / m (SO4) b E 1-b G c .

[0039] In one embodiment, the KG comprises one or more of KF, KCl, KBr, and KI; The ME includes Li2SO4, Li2CO3, LiNO3, LiNO2, Li3PO3, Li3PO4, Li2CrO4, Li2MnO4, Li4SiO4, Li2SiO3, Li3BO3, Li2TeO4, Na2SO4, Na2CO3, NaNO3, NaNO2, Na3PO3, Na3PO4, Na2CrO4, Na2MnO4, Na4SiO4, Na2SiO3, Na3BO3, Na2TeO4, Rb2SO4, Rb2CO3, RbNO3, RbNO2, Rb3PO3, Rb3PO4, Rb2CrO4, Rb2MnO4, Rb4SiO4, Rb2SiO3, Rb3BO3, Rb2TeO4, Cs2SO4, Rb2CO3, CsNO3, CsNO2, Cs3PO3, Cs3PO4, Cs2CrO4, Cs2MnO4, Cs4SiO4, Cs2SiO3, Cs3BO3, Cs2TeO4, BeSO4, BeCO3, Be(NO3)2, Be(NO2)2, Be3(PO3)2, Be3(PO4)2, BeCrO4, BeMnO4, Be2SiO4, BeSiO3, Be3(BO3)2, MgSO4, MgCO3, Mg(NO3)2, Mg(NO2)2, Mg3(PO3)2, Mg3(PO4)2, MgCrO4, MgMnO4, Mg2SiO4, MgSiO3, Mg3(BO3)2, CaSO4, CaCO3, Ca(NO3)2, Ca(NO2)2, Ca3(PO3)2, Ca3(PO4)2, CaCrO4, CaMnO4, Ca2SiO4, CaSiO3, Ca3(BO3)2, SrSO4, SrCO3, Sr(NO3)2, Sr(NO2)2, Sr3(PO3)2, Sr3(PO4)2, SrCrO4, SrMnO4, Sr2SiO4, SrSiO3, Sr3(BO3)2, BaSO4, BaCO3, Ba(NO3)2, Ba(NO2)2, Ba3(PO3)2, Ba3(PO4)2, BaCrO4, BaMnO4, Ba2SiO4, BaSiO3, Ba3(BO3)2, Al2(SO4)3, Al2(CO3)3, Al(NO3)3, Al(NO2)3, AlPO3, AlPO4, Al2(CrO4)3, Al2(MnO4)3, Al4(SiO4)3, Al2(SiO3)3, AlBO3, Al2(TeO4)3, Ga2(SO4)3, Ga2(CO3)3, Ga(NO3)3, Ga(NO2)3, GaPO3, GaPO4, Ga2(CrO4)3, Ga2(MnO4)3, Ga4(SiO4)3,Ga2(SiO3)3, GaBO3, Ga2(TeO4)3, In2(SO4)3, In2(CO3)3, In(NO3)3, In(NO2)3, InPO3, InPO4, In2(CrO4)3, In2(MnO4)3, In4(SiO4)3, In2(SiO3)3, InBO3, In2(TeO4)3, La2(SO4)3, La2(CO3)3, La(NO3)3, La(NO2)3, L One or more of aPO3, LaPO4, La2(CrO4)3, La2(MnO4)3, La4(SiO4)3, La2(SiO3)3, LaBO3, La2(TeO4)3, Y2(SO4)3, Y2(CO3)3, Y(NO3)3, Y(NO2)3, YPO3, YPO4, Y2(CrO4)3, Y2(MnO4)3, Y4(SiO4)3, Y2(SiO3)3, YBO3, Y2(TeO4)3. ,

[0040] In one embodiment, the KE includes one or more of K2SO4, K2CO3, KNO3, KNO2, K3PO3, K3PO4, K2CrO4, K2MnO4, K4SiO4, K2SiO3, K3BO3, and K2TeO4; The MG includes one or more of LiF, LiCl, LiBr, LiI, NaF, NaCl, NaBr, NaI, RbF, RbCl, RbBr, RbI, CsF, CsCl, CsBr, CsI, BeF2, BeCl2, BeBr2, BeI2, MgF2, MgCl2, MgBr2, MgI2, CaF2, CaCl2, CaBr2, CaI2, SrF2, SrCl2, SrBr2, SrI2, BaF2, BaCl2, BaBr2, BaI2, AlF3, AlCl3, AlBr3, AlI3, GaF3, GaCl3, GaBr3, GaI3, InF3, InCl3, InBr3, InI3, LaF3, LaCl3, LaBr3, LaI3, YF3, YCl3, YBr3, and YI3; The MSO4 includes one or more of Li2SO4, Na2SO4, Rb2SO4, Cs2SO4, BeSO4, MgSO4, CaSO4, SrSO4, BaSO4, Al2(SO4)3, Ga2(SO4)3, In2(SO4)3, La2(SO4)3, and Y2(SO4)3.

[0041] The present invention provides a novel polyanion solid electrolyte A which is easy to prepare and can be prepared efficiently. a M(3-a) / m (SO4) b E 1-b G c The method integrates a variety of means to improve the ionic conductivity of solid electrolytes. Through the synergistic effect of various technologies, namely the synergistic strategy of polyanion skeleton construction and heterovalent cation M doping, high entropy effect, lattice distortion, increase of current-carrying A ion vacancies and polyanion rotation coupling are brought about, which synergistically promotes the transmission of ion A in the lattice and significantly improves the ionic conductivity of solid electrolytes. The solid electrolyte prepared by this method has a unique polyanion cluster structure, which is conducive to regulating the spatial distribution and charge balance of anions, bringing about lattice distortion, and is conducive to the formation of highly disordered metal cation distribution and ion transmission channels. The rotation coupling mechanism between various polyanion clusters can also effectively promote the transmission of ions and reduce the energy barrier of ion migration. In addition, doped cations with a valence of +2 or +3 can increase the vacancy concentration in the solid electrolyte, further promote ion transmission, and reduce the activation energy of ion migration.

[0042] The polyanion solid electrolyte prepared by this method has the advantages of high ionic conductivity, good stability, low cost, high efficiency, and suitability for large-scale production. It is suitable for widespread application in the next generation of solid-state batteries and provides a new technical path for the development of low-cost, high-performance solid-state batteries.

[0043] The embodiment of the present invention provides a solid-state battery, which includes the polyanion solid electrolyte described in the embodiment of the present invention. The solid-state battery has high electrochemical performance.

[0044] The present invention will be further described below through several embodiments.

[0045] Example 1 A lithium-based trimer anion SSE Li3(SO4) 0.8 (CO3) 0.1 (CrO4) 0.1 Cl and a preparation method thereof, the preparation method comprising the following steps: LiCl, Li2CO3, Li2CrO4 and Li2SO4 are used as raw materials, and the raw materials are put into a mortar for grinding. The evenly ground raw materials are put into a ball mill, and ball mill beads with a mass ten times that of the raw materials are added. A wet grinding solvent is added, and the solvent is a mixed solution of ethanol and isopropanol (volume ratio 1:1). The ball milling parameters are set to a speed of 200 rpm and a time of 12 hours. The ball-milled material is placed in a vacuum environment at 80°C for heating and drying. Finally, the dried material is placed in a container, transferred to a high-temperature furnace, heated to 500°C at a heating rate of 5°C / min, and kept warm for 12 hours, and then naturally cooled to room temperature. Then the prepared solid is crushed and ground to obtain powdered Li3(SO4)0.8 (CO3) 0.1 (CrO4) 0.1 Cl.

[0046] A lithium-based single polyanion SSE Li3SO4Cl and a preparation method thereof, the preparation method comprising the following steps: With lithium-based trimer anion SSE Li3(SO4) 0.8 (CO3) 0.1 (CrO4) 0.1 The preparation methods of Cl are basically the same, the only difference is that Li3SO4Cl uses LiCl and Li2SO4 as raw materials.

[0047] from Figure 1 From the XRD data, it can be seen that the lithium-based monoanion SSE (i.e., Li3SO4Cl) and the lithium-based trianion SSE (i.e., Li3(SO4) 0.8 (CO3) 0.1 (CrO4) 0.1 The XRD diffraction peaks of lithium-based trimerized anion SSE and lithium-based mono-polyanion SSE do not show the peaks of the raw materials, indicating that the reaction is complete. The diffraction peak positions of the two are basically unchanged, indicating that the lattice structures of the two have not changed significantly and correspond to the same space group. The intensity of some diffraction peaks of lithium-based trimerized anion SSE changes relative to lithium-based mono-polyanion SSE, while the intensity of some diffraction peaks remains unchanged, indicating that certain specific orientations or crystal planes in the lithium-based trimerized anion SSE crystal may be affected by the polyanion clusters. Polyanion clusters of different sizes occupy the same lattice site. The lattice distortion caused by such local size effects often does not affect the lattice constant (peak position), but may cause changes in the scattering intensity on certain crystal planes with specific orientations. Such a high entropy structure provides more possible migration channels for lithium ions. The ionic conductivity of the prepared lithium-based trimerized anion SSE can reach up to 10 -4 S cm -1 Order of magnitude, see Figure 2 , whose impedance is one sixth of that of lithium-based single polyanion SSE.

[0048] Lithium metal symmetric batteries were assembled using lithium-based single polyanion SSE and lithium-based tri-polyanion SSE. The test results showed that the lithium metal symmetric battery assembled with lithium-based tri-polyanion SSE has lower polarization voltage, higher limiting current density and stronger lithium cycling stability. Figure 3 and Figure 4 .

[0049] Using lithium iron phosphate as the positive electrode and lithium metal as the negative electrode, lithium metal full batteries equipped with lithium-based single polyanion SSE and lithium-based tripolyanion SSE were tested. Figure 5As shown, the lithium metal full battery assembled using lithium-based trimerized anion SSE has better cycling performance.

[0050] Example 2 A cation-doped sodium-based double polyanion SSE (Na 2.8 Mg 0.1 (SO4) 0.9 (CO3) 0.1 Cl) and a preparation method thereof, the preparation method comprising the following steps: NaCl, MgCO3 and Na2SO4 are used as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill, ball mill beads with a mass ten times that of the raw materials are added, a wet grinding solvent is added, and the solvent is a mixed solution of ethanol and isopropanol (volume ratio 1:1), and the ball milling parameters are set to a speed of 200 rpm and a time of 12 hours. The ball-milled material is placed in a vacuum environment at 80°C for heating and drying, and finally the dried material is placed in a container, transferred to a high-temperature furnace, heated to 600°C at a heating rate of 8°C / min, and kept warm for 15 hours, and then naturally cooled to room temperature, and then the prepared solid is crushed and ground to obtain powdered Na 2.8 Mg 0.1 (SO4) 0.9 (CO3) 0.1 Cl.

[0051] A sodium-based double polyanion SSE (Na3(SO4) 0.9 (CO3) 0.1 Cl) and a preparation method thereof, the preparation method comprising the following steps: With cation-doped sodium-based double polyanion SSE (Na 2.8 Mg 0.1 (SO4) 0.9 (CO3) 0.1 The preparation method of Na3(SO4) is basically the same, the only difference is that 0.9 (CO3) 0.1 Cl uses NaCl, Na2CO3 and Na2SO4 as raw materials without introducing Mg ions.

[0052] The results of AC impedance spectroscopy are as follows Figure 6 As shown, cation-doped sodium-based double polyanion SSE (Na 2.8 Mg 0.1 (SO4) 0.9 (CO3) 0.1 Compared with sodium-based double polyanion SSE (Na3(SO4) 0.9 (CO3) 0.1Cl) has a lower impedance, indicating that the incorporation of cationic Mg effectively improves the Na ion conductivity.

[0053] The above results indicate that the synergistic strategy of polyanion skeleton construction and heterovalent cation M doping effectively promotes the transport of A ions and improves the ionic conductivity of this type of solid electrolyte.

[0054] In summary, the present invention provides a kind of polyanion solid electrolyte and its preparation method and solid-state battery. The present invention adopts a variety of polyanion clusters to construct the anion skeleton of the solid electrolyte. The lattice distortion brought by the polyanion clusters of different sizes can bring more ion transmission channels. At the same time, the rotation coupling mechanism between the polyanion clusters can also effectively promote the transmission of ions, which is beneficial to improve the ionic conductivity and reduce the activation energy. +2 or +3 valence doped cations can not only introduce cation vacancies, provide more jumping sites for ion migration, but also effectively weaken the Coulomb attraction of lithium, sodium and potassium ions by anions, thereby improving the migration ability of lithium, sodium and potassium ions in the lattice. The present invention adopts a variety of strategies to synergistically enhance the ion transmission ability of the polyanion solid electrolyte, improve ionic conductivity, and reduce activation energy, so that it can be ultimately applied to the preparation of solid-state batteries with high safety and high specific energy.

[0055] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A polyanion solid electrolyte, characterized in that: The chemical formula of the polyanion solid electrolyte is A a M (3-a) / m (SO4) b E 1-b G c ; Wherein, A is one of Li, Na, and K; M is one or more of Li, Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, In, La, and Y, and M and A are different elements; E is SO4 2- ,CO3 2- , NO3 - , NO2 - , PO3 3- ,PO4 3- , CrO4 2- , MnO4 2- , SiO4 4- , SiO3 2- , BO3 3- ,TeO4 2- One or more of; G is one or more of F, Cl, Br, and I; a=0~3, b=0~1, c=0~1, and a, b and c are not 0, and m is the valence state of the M cation.

2. The polyanion solid electrolyte according to claim 1, characterized in that: The polyanion solid electrolyte is in particle form, and the particle size distribution is below 10 μm.

3. The polyanion solid electrolyte according to claim 1, characterized in that: The A a M (3-a) / m (SO4) b E 1- b G c for Na 2.8 Mg 0.1 (SO4) 0.9 (CO3) 0.1 Cl or Li3(SO4) 0.8 (CO3) 0.1 (CrO4) 0.1 Cl.

4. A method for preparing the polyanion solid electrolyte according to claim 1, characterized in that: When A is Li, the chemical formula of the polyanion solid electrolyte is Li a M (3-a) / m (SO4) b E 1-b G c , the Li a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: LiG, ME and Li2SO4 or LiE, MG and MSO4 are used as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the Li a M (3-a) / m (SO4) b E 1-b G c .

5. The method for preparing the polyanion solid electrolyte according to claim 4, characterized in that: The LiG includes one or more of LiF, LiCl, LiBr, and LiI; The ME includes Na2SO4, Na2CO3, NaNO3, NaNO2, Na3PO3, Na3PO4, Na2CrO4, Na2MnO4, Na4SiO4, Na2SiO3, Na3BO3, Na2TeO4, K2SO4, K2CO3, KNO3, KNO2, K3PO3, K3PO4, K2CrO4, K2MnO4, K4SiO4, K2SiO3, K3BO3, K2TeO4, Rb2SO4, Rb2CO3, RbNO3, RbNO2, Rb3PO3, Rb3PO4, Rb2CrO4, Rb2MnO4, Rb4SiO4, Rb2SiO3, Rb3BO3, Rb2TeO4, Cs2SO4, Rb2CO3, CsNO3, CsNO2, Cs3PO3, Cs3PO4, Cs2CrO4, Cs2MnO4, Cs4SiO4, Cs2SiO3, Cs3BO3, Cs2TeO4, BeSO4, BeCO3, Be(NO3)2, Be(NO2)2, Be3(PO3)2, Be3(PO4)2, BeCrO4, BeMnO4, Be2SiO4, BeSiO3, Be3(BO3)2, MgSO4, MgCO3, Mg(NO3)2, Mg(NO2)2, Mg3(PO3)2, Mg3(PO4)2, MgCrO4, MgMnO4, Mg2SiO4, MgSiO3, Mg3(BO3)2, CaSO4, CaCO3, Ca(NO3)2, Ca(NO2)2, Ca3(PO3)2, Ca3(PO4)2, CaCrO4, CaMnO4, Ca2SiO4, CaSiO3, Ca3(BO3)2, SrSO4, SrCO3, Sr(NO3)2, Sr(NO2)2, Sr3(PO3)2, Sr3(PO4)2, SrCrO4, SrMnO4, Sr2SiO4, SrSiO3, Sr3(BO3)2, BaSO4, BaCO3, Ba(NO3)2, Ba(NO2)2, Ba3(PO3)2, Ba3(PO4)2, BaCrO4, BaMnO4, Ba2SiO4, BaSiO3, Ba3(BO3)2, Al2(SO4)3, Al2(CO3)3, Al(NO3)3, Al(NO2)3, AlPO3, AlPO4, Al2(CrO4)3, Al2(MnO4)3, Al4(SiO4)3, Al2(SiO3)3, AlBO3, Al2(TeO4)3, Ga2(SO4)3, Ga2(CO3)3, Ga(NO3)3, Ga(NO2)3, GaPO3, GaPO4, Ga2(CrO4)3, Ga2(MnO4)3, Ga4(SiO4)3, Ga2(SiO3)3, GaBO3,One or more of Ga2(TeO4)3, In2(SO4)3, In2(CO3)3, In(NO3)3, In(NO2)3, InPO3, InPO4, In2(CrO4)3, In2(MnO4)3, In4(SiO4)3, In2(SiO3)3, InBO3, In2(TeO4)3, La2(SO4)3, La2(CO3)3, La(NO3)3, La(NO2)3, LaPO3, LaPO4, La2(CrO4)3, La2(MnO4)3, La4(SiO4)3, La2(SiO3)3, LaBO3, La2(TeO4)3, Y2(SO4)3, Y2(CO3)3, Y(NO3)3, Y(NO2)3, YPO3, YPO4, Y2(CrO4)3, Y2(MnO4)3, Y4(SiO4)3, Y2(SiO3)3, YBO3, Y2(TeO4)3., 6. The method for preparing the polyanion solid electrolyte according to claim 4, characterized in that: The LiE includes one or more of Li2SO4, Li2CO3, LiNO3, LiNO2, Li3PO3, Li3PO4, Li2CrO4, Li2MnO4, Li4SiO4, Li2SiO3, Li3BO3, and Li2TeO4; The MG includes one or more of NaF, NaCl, NaBr, NaI, KF, KCl, KBr, RbF, RbCl, RbBr, RbI, CsF, CsCl, CsBr, CsI, BeF2, BeCl2, BeBr2, BeI2, MgF2, MgCl2, MgBr2, MgI2, CaF2, CaCl2, CaBr2, CaI2, SrF2, SrCl2, SrBr2, SrI2, BaF2, BaCl2, BaBr2, BaI2, AlF3, AlCl3, AlBr3, AlI3, GaF3, GaCl3, GaBr3, GaI3, InF3, InCl3, InBr3, InI3, LaF3, LaCl3, LaBr3, LaI3, YF3, YCl3, YBr3, and YI3; The MSO4 includes one or more of Na2SO4, K2SO4, Rb2SO4, Cs2SO4, BeSO4, MgSO4, CaSO4, SrSO4, BaSO4, Al2(SO4)3, Ga2(SO4)3, In2(SO4)3, La2(SO4)3, and Y2(SO4)3.

7. A method for preparing the polyanion solid electrolyte according to claim 1, characterized in that: When A is Na, the chemical formula of the polyanion solid electrolyte is Na a M (3-a) / m (SO4) b E 1-b G c , the Na a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: NaG, ME and Na2SO4 or NaE, MG and MSO4 are used as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the Na a M (3-a) / m (SO4) b E 1-b G c .

8. The method for preparing the polyanion solid electrolyte according to claim 7, characterized in that: The NaG includes one or more of NaF, NaCl, NaBr, and NaI; The ME includes Li2SO4, Li2CO3, LiNO3, LiNO2, Li3PO3, Li3PO4, Li2CrO4, Li2MnO4, Li4SiO4, Li2SiO3, Li3BO3, Li2TeO4, K2SO4, K2CO3, KNO3, KNO2, K3PO3, K3PO4, K2CrO4, K2MnO4, K4SiO4, K2SiO3, K3BO3, K2TeO4, Rb2SO4, Rb2CO3, RbNO3, RbNO2, Rb3PO3, Rb3PO4, Rb2CrO4, Rb2MnO4, Rb4SiO4, Rb2SiO3, Rb3BO3, Rb2TeO4, Cs2SO4, Rb2CO3, CsNO3, CsNO2, Cs3PO3, Cs3PO4, Cs2CrO4, Cs2MnO4, Cs4SiO4, Cs2SiO3, Cs3BO3, Cs2TeO4, BeSO4, BeCO3, Be(NO3)2, Be(NO2)2, Be3(PO3)2, Be3(PO4)2, BeCrO4, BeMnO4, Be2SiO4, BeSiO3, Be3(BO3)2, MgSO4, MgCO3, Mg(NO3)2, Mg(NO2)2, Mg3(PO3)2, Mg3(PO4)2, MgCrO4, MgMnO4, Mg2SiO4, MgSiO3, Mg3(BO3)2, CaSO4, CaCO3, Ca(NO3)2, Ca(NO2)2, Ca3(PO3)2, Ca3(PO4)2, CaCrO4, CaMnO4, Ca2SiO4, CaSiO3, Ca3(BO3)2, SrSO4, SrCO3, Sr(NO3)2, Sr(NO2)2, Sr3(PO3)2, Sr3(PO4)2, SrCrO4, SrMnO4, Sr2SiO4, SrSiO3, Sr3(BO3)2, BaSO4, BaCO3, Ba(NO3)2, Ba(NO2)2, Ba3(PO3)2, Ba3(PO4)2, BaCrO4, BaMnO4, Ba2SiO4, BaSiO3, Ba3(BO3)2, Al2(SO4)3, Al2(CO3)3, Al(NO3)3, Al(NO2)3, AlPO3, AlPO4, Al2(CrO4)3, Al2(MnO4)3, Al4(SiO4)3, Al2(SiO3)3, AlBO3, Al2(TeO4)3, Ga2(SO4)3, Ga2(CO3)3, Ga(NO3)3, Ga(NO2)3, GaPO3, GaPO4, Ga2(CrO4)3, Ga2(MnO4)3, Ga4(SiO4)3, Ga2(SiO3)3, GaBO3,One or more of Ga2(TeO4)3, In2(SO4)3, In2(CO3)3, In(NO3)3, In(NO2)3, InPO3, InPO4, In2(CrO4)3, In2(MnO4)3, In4(SiO4)3, In2(SiO3)3, InBO3, In2(TeO4)3, La2(SO4)3, La2(CO3)3, La(NO3)3, La(NO2)3, LaPO3, LaPO4, La2(CrO4)3, La2(MnO4)3, La4(SiO4)3, La2(SiO3)3, LaBO3, La2(TeO4)3, Y2(SO4)3, Y2(CO3)3, Y(NO3)3, Y(NO2)3, YPO3, YPO4, Y2(CrO4)3, Y2(MnO4)3, Y4(SiO4)3, Y2(SiO3)3, YBO3, Y2(TeO4)3., 9. A method for preparing the polyanion solid electrolyte according to claim 1, characterized in that: When A is K, the chemical formula of the polyanion solid electrolyte is K a M (3-a) / m (SO4) b E 1-b G c , the K a M (3-a) / m (SO4) b E 1-b G c The preparation method comprises the following steps: Using KG, ME and K2SO4 or KE, MG and MSO4 as raw materials, the raw materials are put into a mortar for grinding, the evenly ground raw materials are put into a ball mill for ball milling, the ball-milled materials are placed in a vacuum environment for heating and drying, and finally the dried materials are heated to a predetermined temperature and then cooled to obtain the K a M (3-a) / m (SO4) b E 1-b G c .

10. A solid-state battery, characterized in that: It comprises the polyanion solid electrolyte according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Solid electrolyte and solid electrolyte battery

    CN115917820A

  • Amorphous solid solution type solid electrolyte, preparation method thereof and solid-state battery

    CN118919829A

  • Solid electrolyte, solid electrolyte layer, and solid electrolyte battery

    CN119343729A

  • Solid ion conductor compound, electrochemical cell, and method of preparing the solid ion conductor compound

    US20240047737A1

Cited By

  • Oxide solid electrolyte, preparation method thereof and solid-state battery

    CN119890436A

  • An oxide solid electrolyte, a preparation method thereof, and a solid-state battery

    CN119890436B